An economic history of India 1707-1857 - Roy, Tirthankar (London Routledge, 2022)
This new edition of An Economic History of Early Modern India extends the timespan of the analysis to incorporate further research. This allows for a more detailed discussion of the rise of the British Empire in South Asia and gives a fuller context for the historiography. In the years between the death of the emperor Aurangzeb (1707) and the Great Rebellion (1857), the Mughal Empire and the states that rose from its ashes declined in wealth and power, and a British Empire emerged in South Asia.
Keywords: India economic conditions 18th century; Economic history; Indian economic business